Effects of Caffeinated Soft Drink on Gonadosomatic Index and Testicular Histology: An In-Vivo Experimental Study in a Wistar Albino Rat Model (Medical Forum Monthly, 2024)
Objective: To determine the effects of caffeinated carbonated soft drinks on the testicular indices, gonadosomatic index (GSI) and histology in an in-vivo Albino Wistar rat model.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Faculty of Medicine and Allied Medical Sciences, Isra University Hyderabad from July 2014 to February 2015.Materials and Methods: The present experimental case control study was conducted at the Department of Anatomy and Postgraduate laboratory of Isra University Hyderabad Sindh. A sample of 20 Wistar Albino rats was selected randomly according to inclusion criteria. Group A (n=10)- tagged as control rats and Group B (n=10)- Experimental rats. Testicular size, weight and histological examination were performed. SPSS 22.0 was used for data analysis at 95% confidence interval (P-value ≤ 0.05).Results: Body weight was increased in the experimental group B rats (P=0.0001). Testicular size and weight were decreased in rats given caffeinated soft drinkers (P= 0.0006). Necrotic areas, Edematous tissues, pyknotic nuclei, hyalinization, luminal defects, reduced seminiferous cell thickness; diameter and tubular lumen were noted in experimental rats.Conclusion: Caffeinated Soft Drink showed deleterious effects on body weight, testicular indices, gonadosomatic index and testicular histology as observed in present in-vivo Wistar Albino Rat model study.